Do We all Acknowledge the Existence of a Market in International Education? - A Viewpoint from the Academic Cooperation Agencies - Race, Julia (2011)
The "Academic Cooperation Association" (ACA) is an independent European organisation dedicated to the support, improvement, management and analysis of academic cooperation within Europe and between Europe and other parts of the world. It was created in July 1993 with the legal status of a non-profit-making international association according to Belgian law and a secretariat in Brussels. The founding President was Professor Eduardo Marçal Grilo, then Director of Cooperation at the Gulbenkian Foundation. The members of ACA are major agencies located in European countries responsible for the promotion of international academic cooperation. There is no Portuguese member of ACA at present.